Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae) - Faleiro, Bárbara T.; Santos, Adalberto J. (Zootaxa, 2019)
The genus Runcinioides is revised, including the redescription of R. argenteus Mello-Leitão, 1929 and R. litteratus (Piza, 1933). The male of R. litteratus is described and illustrated for the first time and Misumenops paranensis (Mello-Leitão, 1932) is here considered a junior synonym of R. argenteus. The known geographic distribution of both species is expanded with the inclusion of new occurrence data. Runcinioides pustulatus Mello-Leitão, 1929 and Runcinioides souzai Soares, 1942 are not related to the other species of the genus, and provisionally considered as incertae sedis.